2006
DOI: 10.1124/jpet.106.112268
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of Common Human Flavin-Containing Monooxygenase 3 Genetic Variants

Abstract: Flavin-containing monooxygenases (FMOs) are important for the disposition of many therapeutics, environmental toxicants, and nutrients. FMO3, the major adult hepatic FMO enzyme, exhibits significant interindividual variation. Eighteen FMO3 single-nucleotide polymorphism (SNP) frequencies were determined in 202 Hispanics (Mexican descent), 201 African Americans, and 200 non-Latino whites. Using expressed recombinant enzyme with methimazole, trimethylamine, sulindac, and ethylenethiourea, the novel structural va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 32 publications
0
49
1
Order By: Relevance
“…If the increased activity observed in vitro is reflected in vivo, individuals with this haplotype, particularly homozygotes, would be expected to metabolize FMO3 substrates more rapidly, leading to a potential reduction in drug efficacy. Although this haplotype is present in relatively high frequency, it is often associated with the linked variant E158K/E308G [39]. In this case an increase in the amount of protein produced, via promoter SNPs, might compensate for an enzyme with lower activity due to coding SNPs.…”
Section: Fmo3mentioning
confidence: 99%
See 2 more Smart Citations
“…If the increased activity observed in vitro is reflected in vivo, individuals with this haplotype, particularly homozygotes, would be expected to metabolize FMO3 substrates more rapidly, leading to a potential reduction in drug efficacy. Although this haplotype is present in relatively high frequency, it is often associated with the linked variant E158K/E308G [39]. In this case an increase in the amount of protein produced, via promoter SNPs, might compensate for an enzyme with lower activity due to coding SNPs.…”
Section: Fmo3mentioning
confidence: 99%
“…Individually, most of the SNPs have little or no effect on enzyme activity [1][2][3][4]38]. Three, however, do affect activity: g.11177C>A(N61K) causes a dramatic decrease in enzyme activity towards four different substrates [39], g.21599T>C(L360P) increases catalytic activity 2-to 5-fold [40] and is the only SNP known to increase FMO3 activity and g.15550C>T(R205C) has a moderate effect on enzyme activity but, interestingly, exhibits substrate inhibition of sulindac sulfide Soxygenation [41]. However, each of the three SNPs is present in low frequency and/or is restricted to single population groups [dbSNP (http://www.ncbi.nlm.nih.gov/projects/SNP)].…”
Section: Fmo3mentioning
confidence: 99%
See 1 more Smart Citation
“…Protein stability is a key feature to protein function (Ye et al, 2006;Zhang et al, 2012), and a missense mutation may affect, besides the secondary structure, its stability, leading to misfolding (Dobson, 2003;Koukouritaki et al, 2007;Zhang et al, 2012). Our findings showed that, unexpectedly, even in missense mutations, without ID regions, when there are no changes in 19.4% of the secondary structures and in 25.6% of the chemical characteristics of the amino acids, the function of GALNS is still suppressed in patients with MPS IVA.…”
Section: Discussionmentioning
confidence: 65%
“…7 Of these, only one, p.Asn61Lys, which occurs at low frequency, results in a severe reduction of enzyme activity. 8 However, some polymorphic variants (eg, p.Glu158Lys and p.Glu308Gly) when present in cis can cause a moderate decrease in enzyme activity. 7,9 When present in the homozygous state, they may cause mild or transient trimethylaminuria, particularly in infants and young children, 10,11 who have low expression of FMO3.…”
Section: Mutational Spectrummentioning
confidence: 99%